PENGARUH SERVICE QUALITY TERHADAP BRAND LOYALTY MELALUI MEDIASI BRAND SATISFACTION DAN BRAND TRUST - Zaenul Muttaqien (Jurnal Bisnis dan Manajemen, 2017)
The research aims examine and analyze the effect of service quality on brand satisfaction, brand trust,and brand loyalty, the research also examine and analyze effect of service quality on brand loyalty by mediate of brand satisfaction and  brand trust. This type of research is explanatory research while collecting primary data through distribution of questionnaires to jamaah in PT.Al Madinna Mutiara Sunnah Kediri as many as  123 jamaah. Sampling technique used is the stratified proportionate random sampling. In this case, the independent variable is service quality, as well as an intervening variable are brand satisfaction and brand trust. While the dependent variable is brand loyalty. The data has been collected then analyzed by using analysis of PLS (Partial Least Square). The results obtained are service quality has effect on brand satisfaction, service quality has effect on brand trust, service quality has no effect on brand loyalty, service quality has effect on brand loyalty by mediate of brand satisfaction, service quality has effect on brand loyalty by mediate of brand trust, brand satisfaction has effect on brand loyalty, brand trust effect on brand loyalty DOI : https://doi.org/10.26905/jbm.v4i1.1717